Multivariable model for predicting acute oral mucositis during combined IMRT and chemotherapy for locally advanced nasopharyngeal cancer patients. (November 2018) - Orlandi, Ester; Iacovelli, Nicola Alessandro; Rancati, Tiziana; Cicchetti, Alessandro; Bossi, Paolo; Pignoli, Emanuele; Bergamini, Cristiana; Licitra, Lisa; Fallai, Carlo; Valdagni, Riccardo; Cavallo, Anna
Highlights: Mean dose to oral cavity impacts most on the duration of acute oral mucositis. Acute oral mucositis severity is also affected by parotid glands mean dose. Body mass index acts as dose-modifying factor for acute oral mucositis severity. Abstract: Introduction/objective: Oral and oropharyngeal mucositis (OM) represents a multifactorial and complex interplay of patient-, tumor-, and treatment-related factors. We aimed to build a predictive model for acute OM for locally advanced nasopharyngeal carcinoma (NPC) patients by combining clinical and dosimetric factors. Materials/methods: A series of consecutive NPC patients treated curatively with IMRT/VMAT + chemotherapy at 70 Gy (2–2.12 Gy/fr) was considered. For each patient, clinical- tumor- and treatment-related data were retrospectively collected. oral cavity (OC) and parotid glands (PG, considered as a single organ) were selected as organs-at-risk (OARs). Acute OM was assessed according to CTCAE v4.0 at baseline and weekly during RT. Two endpoints were considered: grade ≥3 and mean grade ≥1.5. DVHs were reduced to Equivalent Uniform Dose (EUD). Dosimetric and clinical/treatment features selected via LASSO were inserted into a multivariable logistic model. Goodness of fit was evaluated through Hosmer-Lemeshow test and calibration plot. Results: Data were collected for 132 patients. G ≥ 3 and mean G ≥ 1.5 OM were reported in 40 patients (30%). Analyses resulted in a 3-variables model for G ≥ 3 OM, including OC EUD with n = 0.05 (OR = 1.02), PG EUD with n = 1 (OR = 1.06), BMI ≥ 30 (OR = 3.8, for obese patients), and a single variable model for mean G ≥ 1.5 OM, i.e. OC EUD with n = 1 (mean dose) (OR = 1.07). Calibration was good in both cases. Conclusion: OC mean dose was found to impact most on OM duration (mean G ≥ 1.5), while G ≥ 3 OM was associated to a synergic effect between PG mean dose and high dose received by small OC volumes, with BMI acting as a dose-modifying factor.